2009
DOI: 10.1037/a0014366
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil and memory: Effects of modafinil on Morris water maze learning and Pavlovian fear conditioning.

Abstract: Modafinil has been shown to promote wakefulness and some studies suggest the drug can improve cognitive function. Because of many similarities, the mechanism of action may be comparable to classical psychostimulants, although the exact mechanisms of modafinil’s actions in wakefulness and cognitive enhancement are unknown. The current study aims to further examine the effects of modafinil as a cognitive enhancer on hippocampus-dependent memory in mice. A high dose of modafinil (75 mg/kg, i.p.) given before trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
74
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 48 publications
(73 reference statements)
5
74
1
Order By: Relevance
“…A recent study has shown enhanced probe trial performance in the absence of differential escape latency in training trials relative to control in modafinil treated mice (Shuman et al, 2009). Our data display an alternate pattern, with reduced M A N U S C R I P T…”
supporting
confidence: 59%
“…A recent study has shown enhanced probe trial performance in the absence of differential escape latency in training trials relative to control in modafinil treated mice (Shuman et al, 2009). Our data display an alternate pattern, with reduced M A N U S C R I P T…”
supporting
confidence: 59%
“…First, baseline activity prior to any tone or shock on the learning day can be a useful measure of general activity (such as in the open field). Activity during this period, for example, can readily detect the effects of hippocampal lesions or psychostimulant drugs (Anagnostaras et al 1999;Shuman et al 2009). Secondly, the gross motor reactivity to the shock, known as the activity burst or unconditional response, during the actual 2-sec shock can be used as a measure of shock reactivity or pain sensitivity (DeLorey et al 1998;Anagnostaras et al 2000;Shuman et al 2009).…”
Section: Contextual Fear Conditioning On Stereotactically Injected Micementioning
confidence: 99%
“…Activity during this period, for example, can readily detect the effects of hippocampal lesions or psychostimulant drugs (Anagnostaras et al 1999;Shuman et al 2009). Secondly, the gross motor reactivity to the shock, known as the activity burst or unconditional response, during the actual 2-sec shock can be used as a measure of shock reactivity or pain sensitivity (DeLorey et al 1998;Anagnostaras et al 2000;Shuman et al 2009). Finally, the postshock freezing response can be an indicator of the animal's ability to learn, as it is thought to reflect a conditional (i.e., learned) response to the context rather than an unconditional response to the shock (Fanselow 1986).…”
Section: Contextual Fear Conditioning On Stereotactically Injected Micementioning
confidence: 99%
“…One possible explanation for the difference in dosing across fear conditioning and water maze is tolerance [23]. Unlike our earlier fear conditioning experiments where MPH or modafinil was given acutely [11,22], water maze training involves repeated stimulant injections. We examined this possibility by chronically administering 10 mg/kg MPH and then testing its effect on fear learning.…”
Section: Introductionmentioning
confidence: 95%
“…This hippocampal-dependent task requires subjects to use distal spatial cues to locate a fixed hidden platform in order to escape from a pool of opaque water [19][20][21]. In earlier work, we found that a much higher dose of the atypical psychostimulant modafinil [1] was necessary to enhance water maze acquisition (75 mg/kg) as compared to fear conditioning (0.75 mg/kg) [22]. One possible explanation for the difference in dosing across fear conditioning and water maze is tolerance [23].…”
Section: Introductionmentioning
confidence: 96%